Designing and implementing Agricultural Innovation Funds : Lessons from Competitive Research and Matching Grant Projects - World Bank (Washington, DC, 2013)
Many countries are using innovation funds in the agricultural sector to support innovators and their links to public institutions, private entrepreneurs, and other actors, such as groups of rural producers. These funds create platforms for innovative activity by providing incentives for quality and collaboration. This report synthesizes experience with the two main innovation funds that the World Bank has used to fund agricultural innovation, competitive research grants and matching grants, and offers lessons and guidelines for designing and implementing them. Although the report draws extensively on experience with World Bank investments, the lessons are relevant in other contexts. The practical aspects of designing and implementing successful grant schemes are emphasized throughout.